TRAINING OF APPLICANTS FOR PROFESSIONAL HIGHER EDUCATION IN THE SPECIALITY 023 ‘FINE ARTS, DECORATIVE ARTS, RESTORATION’ (Innovative professional education, 2025)
The article outlines the issue of the relevance of practical training of professional pre-higher education applicants in the specialty 023 «Fine arts, decorative arts, restoration», capable of solving typical specialized tasks and practical problems in the field of fine arts, decorative arts, or in the learning process, which involves the application of certain theories, provisions and methods of artistic activity in the context of European integration changes and educational transformations.
Keywords: art teacher, art education, artistic and aesthetic education, professional teacher training, teaching methods and techniques, pedagogical practice